College Students' Understanding of Digital Economic Crimes: A Study on Perceptions and Challenges in Law Enforcement (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2024)
Digital economic crimes pose a significant challenge in the rapidly evolving technological era, particularly for younger generations actively engaged in digital activities. This study aims to explore students’ understanding of digital economic crimes, the challenges in law enforcement, and their critiques of existing regulations. The research adopts a qualitative design with a phenomenological approach, involving 10 students from the Faculty of Islamic Economics and Business, majoring in Sharia Financial Management, as informants. Data were collected through semi-structured interviews conducted in two sessions of 20 minutes each. Thematic analysis was employed to identify key themes. The findings reveal that while students are aware of digital risks, such as online fraud and identity theft, their preventive measures remain limited. Informants also identified challenges in law enforcement, including the technological gap between offenders and law enforcement agencies, lack of inter-agency coordination, and inadequate technological training for law enforcement personnel. Moreover, existing regulations, such as the Electronic Information and Transactions Law (UU ITE), are deemed insufficient in addressing the complexities of digital economic crimes. This study highlights the importance of enhancing digital literacy among students, reforming regulations to better adapt to technological advancements, and improving technological capacity and inter-agency coordination in law enforcement to establish a safer digital ecosystem.